Surgical Outcomes of Decompressive Craniectomy among Patients with Severe Traumatic Brain Injury. A single-center Retrospective Study, Yemen - Shamsaldin, Mohamed; Me’asar, Mojahed; Siaour, Hael S.; Al-Aswadi, Abdulghani; Alashhab, Noofel; Alfakih, Sakhr (Journal of Amran University, 2024)
Decompressive craniectomy (DC) is a surgical procedure used to alleviate severe intracranial pressure and its complications in cases of traumatic brain injury (TBI). This retrospective study explores the surgical outcomes of DC performed on patients with severe TBI at 48 Modern Hospital in Sana'a, Yemen. The analysis focused on 31 male patients, aged 17 to 65, who underwent DC between January 2020 and December 2021. Collected data included patient demographics, mechanisms of injury, Glasgow Coma Scale (GCS) scores, CT scan findings, treatment methods, and the time between injury and hospital admission. The outcomes were assessed using an extended Glasgow Outcome Scale (GOS-E) one year after surgery via structured phone interviews. All participants in the study were male, predominantly within the adult age range. The most common cause of injury identified was gunshot wounds, accounting for 48.4% of cases. The outcomes revealed that 48.4% of patients made a full recovery, 25.8% experienced disabilities, and 25.8% died. Poor outcomes were significantly linked to lower GCS scores upon admission, hemiplegia, abnormal pupillary responses, and extended hospital stays. The findings indicate that, while DC can lead to positive outcomes for TBI patients, factors such as initial GCS, pupil dilation, and hemiplegia serve as indicators of a poor prognosis. Optimal timing for the surgery may further improve results.